2008
DOI: 10.1002/14651858.cd003189.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Granulopoiesis-stimulating factors to prevent adverse effects in the treatment of malignant lymphoma

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(22 citation statements)
references
References 94 publications
0
22
0
Order By: Relevance
“…Hematopoietic colonystimulating factors (CSFs) are critical to some aspects of modern chemotherapy, such as dose-dense chemotherapy, induction therapy in leukemia, and intense therapy for lymphoma. 23 Yet the expense is tremendous and the clinical benefit smaller than hoped; for instance, survival is not improved by using CSFs in two of the most chemotherapy- sensitive cancers, lymphoma 24 and small-cell lung cancer. 25 …”
Section: Changing Oncologists’ Behaviormentioning
confidence: 99%
“…Hematopoietic colonystimulating factors (CSFs) are critical to some aspects of modern chemotherapy, such as dose-dense chemotherapy, induction therapy in leukemia, and intense therapy for lymphoma. 23 Yet the expense is tremendous and the clinical benefit smaller than hoped; for instance, survival is not improved by using CSFs in two of the most chemotherapy- sensitive cancers, lymphoma 24 and small-cell lung cancer. 25 …”
Section: Changing Oncologists’ Behaviormentioning
confidence: 99%
“…Further, patients with a malignant disease, more frequently suffered from SIRS or bacteremic/fungemic sepsis, but less frequently from nonbacteremic/fungemic sepsis. This finding could be based on an immunosuppression and therefore reduced ability to control a local infection [20][21][22]. Further, a malignant disease itself or antineoplastic chemotherapy are causative factors for developing a SIRS syndrome without any infection, e.g., neutropenic fever [23].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 2 reported severe reactions, 1 was associated with an EDTA-containing formula, which was therefore changed. GM-CSF and G-CSF have comparable toxicity profile, albeit a higher rate of injection site reactions with the use of the former 19 . The absence of studies using comparable doses of G-CSF does not allow us to determine whether the reported discontinuation rate has to be considered high.…”
Section: Discussionmentioning
confidence: 97%